Clinical and histopathological correlates of intestinal repair in preterm infants following surgical necrotizing enterocolitis. (30th December 2022) - Garg, Parvesh Mohan; Middleton, Charles; Zhang, Mengna; Paschal, Jaslyn L.; Kurundkar, Ashish R.; Sonani, Hardik; Varshney, Neha; Hillegass, William B.
Abstract: Objective: We sought to determine the clinical and histopathological factors linked with intestinal repair and its correlation with clinical outcomes in preterm infants following surgical necrotizing enterocolitis (NEC). Methods: A retrospective study has compared clinical and histopathological characteristics between preterm infants with histopathological reparative changes versus non-reparative changes in resected intestinal tissue following surgical treatment of NEC. Reparative changes were defined as microscopic evidence of neovascularization, increased fibroblasts or myofibroblasts, and epithelial regeneration during histopathological examination of the most affected area of resected intestinal tissue. Results: The infants with reparative changes (53/148) had significantly lower median birth weight (725 [650−963] vs. 920 [690−1320]; p = .018), higher likelihood of patent ductus arteriosus (38/53 [71.7%] vs. 48/95 [50.5%]; p = .012), longer TPN days (99 [56−147] vs. 76.5 [39−112.5]; p = .034), higher CRP levels (7.3 [3.2−13] vs. 2.6 [1.1−7.8]; p = .011) at NEC onset, and more short bowel syndrome (27/53 [54.0%] vs. 28/95 [32.2%]; p = .012). Those with reparative changes also received more Penrose drain therapy (21/53 [39.6%] vs. 14/95 [14.7%]; p = .011) and had a longer median time to laparotomy (108 h [28−216] vs. 24 [12−96]; p = .003). Epithelial regeneration observed in 6/53 (11.3%) infants lagged fibroblast proliferation and neovascularization changes in the submucosa/muscularis intestinal layers. On a multivariable logistic regression model which included histopathological and clinical factors, inflammation with a percentage <25% area involvement, time from NEC diagnosis to surgery, and Apgar score < 6 at 5 min were independently and significantly associated with higher odds reparative changes. Conclusion: In neonates with surgical NEC, the histopathological findings in the resected bowel are significantly associated with clinical characteristics, other histopathological findings, and outcomes. The presence of reparative changes consistent with healing is significantly associated with Apgar score, Penrose drain therapy, longer time from NEC diagnosis to surgery, and lower burden of inflammation in the resected bowel tissue in multivariable analyses. Routine histopathological grading of resected bowel and optimal use of Penrose drain therapy warrant further investigation in the care of neonates with surgical NEC.